Transversus abdominis plane block for pain relief in patients undergoing in endoscopic repair of abdominal wall hernia: A comparative, randomised double-blind prospective study - Aparna Sinha; Lakshmi Jayaraman; Dinesh Punhani; Pradeep Chowbey (Journal of Minimal Access Surgery, 2018)
Introduction: Transversus abdominis plane (TAP) block is now a well-established technique in post-operative analgesia for lower abdominal surgeries. We evaluated the effect of ultrasound-guided TAP block on recovery parameters in patients undergoing endoscopic repair of abdominal wall hernia. Methods: Thirty adults were randomised to receive either ropivacaine with dexmedetomidine (TR) or saline (TP) in TAP block, before emergence from anaesthesia. The patients were assessed for pain relief, sedation, time to ambulate (TA), discharge readiness (DR), postoperative opioid requirement and any adverse events. Results: The median visual analogue scale pain score of the study group (TR) and the control group (TP) showed a significant difference at all time points. TA was 5.3 ± 0.5 (TR) versus 7.4 ± 0.8 (TP), P< 0.001 and DR was 7.5 ± 0.9 (TR) versus 8.9 ± 0.6 (TP), P< 0.001 in hours. No adverse events were observed in any group. Conclusion: This study demonstrates that TAP block is a feasible option for pain relief following endoscopic repair of abdominal wall hernias. It produces markedly improved pain scores and promotes early ambulation leading to greater patient satisfaction and earlier discharge.